Pengaruh Discovery Learning Terhadap Aktivitas Belajar Siswa Pada Pembelajaran Teknik Dasar Sepak Bola Kelas VIII Di SMP Tunas Dharma - Abdillah, Yusha Nura; Kurniawan, Febi (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to determine the influence of the Discovery Learning model on students' learning activities in basic football technique lessons for eighth-grade students at SMP Tunas Dharma. The background of this research is based on the low level of student learning activity and the lack of variety in teaching models applied by teachers, resulting in students tending to be passive during the learning process. Discovery Learning was chosen because it emphasizes student-centered activities to discover concepts through observation, exploration, and drawing conclusions independently. This research employed an experimental method with a one-group pretest-posttest design. The research sample involved all 54 eighth-grade students at SMP Tunas Dharma. The research instruments were tests of learning activity in basic football techniques including passing, dribbling, shooting, and heading. The results showed an increase in students' learning activities after the implementation of the Discovery Learning model. This was evidenced by higher average posttest scores compared to pretest scores. Based on data analysis, it can be concluded that the Discovery Learning model positively influences students' learning activities in basic football technique lessons at SMP Tunas Dharma. This study is expected to serve as a reference for physical education teachers in selecting appropriate teaching models to enhance students' activity and learning outcomes.